A benefit-sharing model for hydropower projects based on stakeholder input-output analysis: A case study of the Xiluodu Project in China. (April 2018) - Xia, Bingqing; Qiang, Maoshan; Chen, Wenchao; Fan, Qixiang; Jiang, Hanchen; An, Nan
Abstract: The rich hydro resources and global pressures of greenhouse gas emission have promoted the rapid development of hydropower projects in China. However, the benefit distribution unfairness in hydropower projects leads to problems such as resettlement conflicts, which significantly hinder the sustainable development of hydro resources. In order to determine a reasonable benefit sharing policy system, this study employs a new perspective, which treats the reservoir migrants as a formal project stakeholder rather than the passive "compensation receivers" previous practices have considered them to be. From this perspective, this study 1) identifies the stakeholders of hydropower projects and their input/output factors based on stakeholder theories, and highlights the four most important core stakeholders, i.e., government, hydropower generation enterprises, reservoir migrants, and power grid enterprises; 2) designs a specific calculation method for the four core project stakeholders' cash flows and establishes a quantitative benefit-sharing model based on the input-output analysis; and 3) employs the Xiluodu Project in China as a case study to demonstrate the feasibility and effectiveness of the proposed method. Theoretically, the change in reservoir migrants' status in the project delivery framework provides a new perspective for benefit sharing and resettlement studies. Practically, this study establishes a feasible quantitative tool for the description and assessment of benefit sharing systems, and the overall assessment of hydropower projects. The results of the case study show that, under the current benefit distribution policy of China, yields of reservoir migrants are significantly lower than those of other core stakeholders. The results also indicate that, by increasing resettlement compensation standards and slightly adjusting the electricity generation price, all core stakeholders' yields can reach a more rational and fair level.